Effects of ultrasonic specific energy on time-dependent inactivation rate of proteus mirabilis and streptococcus sanguinis - GÖKALSIN, BARIŞ; SESAL, NÜZHET CENK (My University, 2023)
Ultrasound has been used as an alternative and enhancer approach for the inhibition of microorganisms in recent years. The purpose of the current study was to determine the inactivation of Streptococcus sanguinis and Proteus mirabilis bacteria species via ultrasound. For this purpose, bacterial suspensions with 5x103, 1.5x104, and 3x104 colony forming unit (cfu/ml) concentrations were ultra-sonicated with 30 kHz frequency and 100 W power ultrasound for various sonication time periods. As a result, time-dependent inhibition rates were observed with bacteria concentration differences. The specific energy (γ) of different concentrations of S. sanguinis and P. mirabilis was also calculated. The rate constant of ultrasonic inhibition was evaluated in the linear region against sonication time. Then, the t-test was applied to all of the data. The results of 5x103, 1.5x104, and 3x104 cfu/ml for S. sanguinis and P. mirabilis were statistically significant at <p= 0.02, 0.02, 0.006 for S. sanguinis, and at <p=0.003, 0.004, 0.003 for P. mirabilis, respectively.
Keywords: Tıp; Mikrobiyoloji ve Klinik Mikrobiyoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Microbiology and Clinical Microbiology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Mikrobiyoloji; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; MİKROBİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; Genel Biyokimya, Genetik ve Moleküler Biyoloji; Microbiology; General Biochemistry, Genetics and Molecular Biology; bacteria; Proteus mirabilis; specific energy; Streptococcus sanguinis; time-dependent inactivation; ultrasound